Auditoría de gestión para el área de negocios en el proceso de crédito del Banco VISIOFUND agencia Tulcán - Urresta Rosero, Ginna Gabriela (2019)
The present investigation originated with the objective of developing a management audil of the business area in the loan process of Banco Visionfund Agencia Tulcán, to evaluate the results and establish the level of effectiveness, efficiency and quality in the fulfllment of organizational objectives . This work was based on the modality of qualitative-quantitative research and methods were used field research, bibliography supported by empirical, theoretical methods and using various research techniques that allowed the collection of information such as interview, survey, observation direct and the application of instruments such as the questionnaire, the interview guide and the observation form. The management audit was carried out using a systemic procedure applying the preliminary and specific planning audit phases with the collection of company information and evaluation of the internal control system. In the execution, an audit program was established and the audit findings were determined. They are included in the report and are presented in the results communication phase. The deficiencies found in the development of activities in the business area in the credit process are due to the non-compliance of credit processes established in the manual.